Dicas para uma boa deglutição do hóspede à soleira de sua porta: as heterotopias invisíveis dos moradores em situação de rua de Campinas - Oda, Lucas Kiyoharu Sanches [UNIFESP] (2019)
It is estimated that there are more than 103,000 homeless people in Brazil. This phenomenon, which originated and increased each year for various reasons, is largely evidence of the collapse of a society based on capitalist consumption. This thesis is part of the Foucauldian concept of heterotopia to propose that the homeless, in their process of exile from society, migrate to a heterotopia that coexists with our reality, but is invisible to the eyes of the people who are just passing through the streets. It is in this invisible heterotopia that the homeless live in the street, in a greater abandonment than that of a foreigner, because to them hospitality does not apply, since it is to them that the laws are denied in a state of exception that abandons them. The proposal, derived from the studies of hospitality of Derrida and Schérer, as well as of the anthropophagy of Oswald de Andrade, is to make it possible an excessive and unconditional hospitality to the homeless people so that, after devoured in an anthropophagic banquet, they can give us an exotopic vision of the society with many sharper contours than that of our perspective, within the sovereign ban, can ever perceive.